P2_6 The influence of agricultural emissions on global warming - Gorley, Michael; Anand, Jasdeep; Weaver, Iain; Buccheri, Alexander (Physics Special Topics, 2009)
<span style="font-size: 10pt; font-family: ";Calibri";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Current estimates on the influence anthropogenic greenhouse gas emissions on global warming may have neglected the influence the agricultural emissions have, especially given the attempts to phase in biofuels in the transport industry. This paper investigates the effect emissions of nitrous oxide (N2O) may have by calculating its Global Warming Potential (GWP) over the next 100 years. However, due to a lack of data a final judgment on the effect growing more biofuels would have on climate change could not be made